Total Synthesis and Conformational Study of Callyaerin A: Anti‐Tubercular Cyclic Peptide Bearing a Rare Rigidifying (Z)‐2, 3‐ Diaminoacrylamide Moiety. (14th February 2018) - Zhang, Shengping; De Leon Rodriguez, Luis M.; Leung, Ivanhoe K. H.; Cook, Gregory M.; Harris, Paul W. R.; Brimble, Margaret A.
Abstract: The first synthesis of the anti‐TB cyclic peptide callyaerin A (1 ), containing a rare ( Z )‐2, 3‐diaminoacrylamide bridging motif, is reported. Fmoc‐formylglycine‐diethylacetal was used as a masked equivalent of formylglycine in the synthesis of the linear precursor to1 . Intramolecular cyclization between the formylglycine residue and the N‐terminal amine in the linear peptide precursor afforded the macrocyclic natural product1 . Synthetic1 possessed potent anti‐TB activity (MIC100 =32 μm ) while its all‐amide congener was inactive. Variable‐temperature NMR studies of both the natural product and its all‐amide analogue revealed the extraordinary rigidity imposed by this diaminoacrylamide unit on peptide conformation. The work reported herein pinpoints the intrinsic role that the ( Z )‐2, 3‐diaminoacrylamide moiety confers on peptide bioactivity.